Time-Programmed Guarana Extract-EGCG-Konjac Glucomannan Matrix for Weight Management: Formulation Performance, Satiety Signaling, and Translational Evidence - Yassine, Jabar; Semenza, Gregg L.; Blake, Ethan (International Journal of Agriculture and Food Sciences Research, 2026)
Background: Obesity remains a major global health problem, and practical weight-management products often fail because thermogenic ingredients, catechins, and satiety fibers are combined without a delivery system that protects labile actives or coordinates gastrointestinal exposure [1]. We therefore evaluated a time-programmed guarana extract-EGCG-konjac glucomannan (KGM) matrix and interpreted its disclosed formulation-performance dataset alongside published human and mechanistic evidence. Methods: We reviewed the disclosed composition, comparator results, gastrointestinal release behavior, animal-model outcomes, and short-term volunteer satiety observations, and we complemented these data with a structured PubMed- and WHO-based literature search through March 2026. Results: In the disclosed dataset, 2-h EGCG retention in simulated gastric fluid remained 83.9–88.7% for qualified formulations but only 31.7% for the parameter-mismatched comparator. Qualified matrices sustained intestinal release (65.8–71.2% at 6 h) and preserved near-complete colonic release (96.7–98.1% at 12 h). In obese mice, the benchmark embodiment reduced body weight by 21.3%, body-fat percentage by 32.7%, and food intake by 28.4% versus model control, with concurrent rises in GLP-1 and fecal butyrate. Published studies provide biologically concordant support: EGCG-caffeine/guarana mixtures increased 24-h energy expenditure in a randomized crossover trial [2], low-dose EGCG increased postprandial fat oxidation in obese men [3], gelled KGM reduced appetite and energy intake in healthy adults [5], and a 2024 dose-response meta-analysis reported significant reductions in body mass, BMI, and body-fat percentage with green tea extract supplementation [4]. Conclusion: We found that the differentiating value of the NVTIA platform lies primarily in matrix architecture rather than ingredient listing alone. The combined evidence supports a formulation-level rationale for staged satiety and metabolic support, while confirming that independent clinical validation remains necessary.